Laminin-Mediated Interactions in Thymocyte Migration and Development - Savino, Wilson; Mendes-da-Cruz, Daniella Arêas; Golbert, Daiane Cristina Ferreira; Riederer, Ingo; Cotta-de-Almeida, Vinicius (Frontiers in Immunology, 2015)
Intrathymic T-cell differentiation is a key process for the development and maintenance of cell-mediated immunity, and occurs concomitantly to highly regulated migratory events. We have proposed a multivectorial model for describing intrathymic thymocyte migration. One of the individual vectors comprises interactions mediated by laminins (LMs), a heterotrimeric protein family of the extracellular matrix. Several LMs are expressed in the thymus, being produced by microenvironmental cells, particularly thymic epithelial cells (TECs). Also, thymocytes and epithelial cells express integrin-type LM receptors. Functionally, it has been reported that the dy/dy mutant mouse (lacking the LM isoform 211) exhibits defective thymocyte differentiation. Several data show haptotactic effects of LMs upon thymocytes, as well as their adhesion on TECs; both effects being prevented by anti-LM or anti-LM receptor antibodies. Interestingly, LM synergizes with chemokines to enhance thymocyte migration, whereas classe-3 semaphorins and B ephrins, which exhibit chemorepulsive effects in the thymus, downregulate LM-mediated migratory responses of thymocytes. More recently, we showed that knocking down the ITGA6 gene (which encodes the α6 integrin chain of LM receptors) in human TECs modulates a large number of cell migration-related genes and results in changes of adhesion pattern of thymocytes onto the thymic epithelium. Overall, LM-mediated interactions can be placed at the cross-road of the multivectorial process of thymocyte migration, with a direct influence per se, as well as by modulating other molecular interactions associated with the intrathymic-trafficking events.